Increasing rate of hospitalization for severe peptic ulcer in digestive disease emergencies after the pandemic. Issue 48 (2nd December 2022) - Jian, Chenxing; Zhou, Zili; Yang, Chunkang; Zhao, Ning; Bao, Haijun; Han, Shengbo; Chen, Jinhuang; Shu, Xiaogang
Abstract : Since December 2019, the novel coronavirus has spread worldwide, affecting more than 510 million people, with more than 6 million deaths. However, some of the potential effects of the pandemic have not been thoroughly studied. We collected data from 2 regional emergency centers from May to November for the years 2015 to 2019, before the pandemic, and from May to November 2020, after the pandemic. We evaluated the incidence of each major type of digestive disease before and after the pandemic in adults at the 2 hospitals, which experienced coronavirus disease 2019 outbreaks with varying severity. A total of 11, 394 patients were enrolled in the study Affiliated Hospital of Putian University (PUTIAN, n = 5503) Union Hospital, Tongji Medical college, Huazhong University of Science and Technology (UNION, n = 5891), and the proportion of male patients was approximately the same at both hospitals, with 3360 (61.1%) and 3680 (62.5%), respectively. The average ages of the patients were 55.8 ± 18.4 years PUTIAN and 54.3 ± 15.8 years UNION. The numbers of patients at the 2 hospitals increased steadily, but in 2020, the number of patients at UNION declined. The baseline characteristics of the 2 groups at the 2 hospitals showed significant differences for age before and after the pandemic but not for sex. The constituent ratios of diseases in each year in the 2 hospitals differed. The number of patients with peptic ulcers in 2020 was significantly different from those in each year from 2015 to 2019 (PUTIAN 2015‐2020, 15.0%, 18.2%, 14.9%, 16.9%, 19.5%, 34.9%; UNION 2015‐2020, 29.2%, 32.5%, 29.3%, 29.4%, 29.7%, 41.3%, respectively). The rates of peptic ulcer increased dramatically in both hospitals in 2020. An increase in the incidence of severe peptic ulcer was observed after the pandemic compared to the same period before the pandemic. Therefore, these factors should be considered in the formulation of public health strategies and the allocation of medical resources in the post pandemic era.